Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$ x^2 + y^2 = 4x+4$

How to put it in the standard form: $(x-a)^2 + (y-b)^2 = r^2$

share|cite|improve this question
up vote 5 down vote accepted

$(x-a)^2+(y-b)^2=r^2\implies x^2+y^2-2ax-2by+a^2+b^2-r^2=0$

Comparing with, $x^2+y^2-4x-4=0$

$b=0$ (coefficient of $y$)

$2a=4\implies a=2$ (coefficient of $x$)

$a^2+b^2-r^2=-4,2^2+0^2-r^2=-4,r^2=8$ (constant term)

So, $(x-2)^2+(y-0)^2=(2\sqrt 2)^2$

Or directly, $x^2+y^2-4x-4=(x)^2-2\cdot x\cdot 2+(2)^2+(y)^2-4-4$ $=(x-2)^2+(y)^2-(2\sqrt 2)^2$

So, $(x-2)^2+(y)^2-(2\sqrt 2)^2=0$ or $(x-2)^2+(y)^2=(2\sqrt 2)^2$

share|cite|improve this answer
Thank you, I understand. – JohnPhteven Oct 23 '12 at 9:57
@ZafarS, welcome! – lab bhattacharjee Oct 23 '12 at 10:01

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.